(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
The article analyzes the forms and means of forming the image of “Soviet women”, which were widely used in Soviet times to demonstrate the virtues and achievements of the socialist system, as well as the use of photography in its propaganda. The importance and role of photographs, considered a means of visual propaganda, in influencing public consciousness and shaping public opinion is revealed.